Analysis of two-factor authentication plugins for WordPress - Kolomiitsev, S.O.; Sievierinov О.V.; Fedorchenko, V.M.; Sukhoteplyi, V.M. (Radiotekhnika, 2023)
The purpose of this article is to analyze existing two-factor authentication plugins to assess their effectiveness. Due to the lack of substantial protection against unauthorized access in the WordPress system, it becomes vulnerable to types of attacks such as dictionary attacks and brute force attacks. To address this issue, plugins for two-factor authentication are used. The article examines the most popular two-factor authentication plugins to evaluate the level of security they provide. This article will be beneficial for website owners and administrators using WordPress who need to protect their resources against unauthorized access.